Antioxidant and anti-ulcer effect of Elaeis Guineensis Jacq. (Oil Palm) leaves ethanolic extract on experimental rats / Nurusyifa’ Abd Rahim - Abd Rahim, Nurusyifa’ (2016)
The aim of the study was to determine the anti-ulcer effect of Elaeis guineensis Jacq. (Oil palm) leaves ethanolic extract on ethanol-induced ulcer in rats. In the present study, the rats were pre-treated with E. guineensis leaves (100, 200 and 500 mg/kg b.wt.). The phytochemical contents of the leaves were screened using Gas Chromatography Mass Spectrophotometer (GC-MS). Meanwhile, antioxidant activity was evaluated using 1, 1- diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay with five different concentrations (0.01, 0.05, 0.1, 0.15 and 0.2 mg/mL). From the results, the rats pre-treated with 100 mg/kg b.wt. Significantly (p<0.05) showed gastroprotective effect where only a small area of hemorrhagic lesions appeared on the gastric mucosal layer. Based on the phytochemical screening by GC-MS, the presence of phytol was detected. Phytol is known as diterpenoids, which can be found in chlorophyll and tocopherol. They are known as strong immunomodulatory agent, which is known as one of the components that can increase human immune system in fighting antigens. Antioxidant assay exhibited good antioxidant activity from the ethanolic extract with IC50 value of 0.0817 mg/mL. IC50 value less than 10 mg/mL is considered as an effective antioxidant. The extract at high concentration (0.2 mg/mL) showed the highest percentage of DPPH inhibition by antioxidant with 67.06%. Thus, explaining the extract at high concentration has higher antioxidant activity compare to lower concentration. In the anti-ulcer study, an increase in concentration E. guineensis (0.2 mg/mL), led to an increase in ulcer area. This could be due to the fact that phytol are potentially toxic at high concentration, although they are also good immunomodulatory agents. The extract at low concentration showed an effective gastroprotective activity as compared to the extracts at higher concentrations. Thus, E. guineensis leaves appear to have therapeutic potential in preventing gastric ulceration induced by ethanol.